Elles [videorecording (DVD)] - Szumowska, Małgorzata, 1973-; Binoche, Juliette, 1964-; Demoustier, Anaïs, 1987-; Kulig, Joanna, 1982-; Janda, Krystyna; Lencquesaing, Louis-Dominique de; Chyra, Andrzej, 1964- (Kino Lorber, 2012)
A journalist researching an article on student prostitution for the French edition of ELLE magazine finds herself drawn to two young women. The stories these seemingly well-adjusted girls share force the middle-aged writer to examine her own life, family and sexuality.